Innovative Anti-Corruption Education in the Digital Age: A Team-Based and Student-Focussed - Ulum, Bachrul; Astutik, Leny Suryaning; Putra, A.A. Putu Eka; Zaini, Moh.; Ali, Makki (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2025)
Innovative anti-corruption education in the digital age requires integrating technology to effectively engage young people in understanding corruption’s dangers. This study explores the application of a Learning Management System (LMS) in anti-corruption education through a student-centered, team-based project learning approach. A qualitative case study was conducted at Universitas Bhinneka PGRI and STKIP PGRI Trenggalek, involving 55 students, two lecturers, and leaders of related universities. Data were gathered via interviews, documentation, and observations and analyzed interactively. The results indicated that LMS facilitated increased student engagement in anti-corruption learning, particularly through discussion forums and project-based activities. However, challenges such as technology access and student comfort with digital learning emerged. The study recommends expanding LMS usage in anti-corruption education, with additional support through technology training and improved accessibility. This approach can enhance the effectiveness, relevance, and sustainability of anti-corruption education, better equipping future generations to combat corruption.